Qualidade na educação: um estudo de caso do Colégio Estadual Augusto Meyer no município de Esteio/RS - Kingeski, Luiz Felipe César (Universidade do Vale do Rio dos Sinos, 2014)
This case study seeks to understand, based on the articulation of educational policies, school history and management processes, how is the quality of education at Colégio Estadual Au-gusto Meyer in the city of Esteio/RS. The main object focuses on the understanding of the elements that characterize the quality of education in the institution. The specific objectives address the history of the institution both from the actors and documents perspectives, and the analysis of the management processes undertaken in the school, aiming at the issue of educa-tion quality. A case study based on the ethnographic inspiration was conducted as the meth-odology. The data were collected from interviews, school’s library collections and official documents. The interviews were conducted with managers and former teachers and the an-swers were compared to the bibliographic data and theoretical foundation on the quality of education. It is understood that the search for quality in education is closely linked to a worldview that points the school as a source of knowledge/learning. The narrative concerning the school's history was organized in three phases and involves the period between 1973 and 2012, covering the entire school history from its foundation to the present day. It was also designated four management processes undertaken at Colégio Estadual Augusto Meyer, which focus on the education quality in infrastructure, human Resources, management and organization of schoolwork and the school-community relationship. Each process analyzes the quality of education with a different focus, but all of them are related to the school's history. It also analyzes their management processes. As a result it was identified that the various adopt-ed educational policies, the undertaken management processes and the history of the school feature quality factors. Concerning the phases of the institution, it was found in the beginning a school with high investment in a model program for the time. In the 1980s it goes through a crisis during the country's democratization process and the increasing of education and access to school. In a third moment, it resumes the quality with a new management and entrepreneur group. The quality of Colégio Estadual Augusto Meyer is not a process characterized only by having a differentiated structure inherited from Polyvalent Schools, neither by the educational policies of the periods and the manager group of a certain phase. The quality of Colégio Es-tadual Augusto Meyer can be attributed to the interconnected set of all these factors.
Keywords: Políticas educacionais; História das instituições escolares; Qualidade da educação; Escolas polivalentes; Escola pública estadual; Educational policies; History of school institutions; Quality of education; Polyvalent schools; State public school; ACCNPQ::Ciências Humanas::Educação